Colorectal cancer screening behaviors among South Asian immigrants in Canada: a qualitative study. Issue 2 (15th June 2015) - Crawford, Joanne; Ahmad, Farah; Beaton, Dorcas E.; Bierman, Arlene S.
Abstract : Purpose: – The purpose of this paper is to gain an in-depth understanding of beliefs, attitudes, and reasons for decision making about colorectal cancer (CRC) screening among South Asian (SA) immigrants. Design/methodology/approach: – Six focus groups conducted in English, Punjabi, and Urdu were held with 42 SA immigrants, 50-74 years old and at average risk for CRC, from November 2012 to May 2013. All focus group discussions were audio-taped and transcribed verbatim. Data analysis used an inductive and systematic approach employing constant comparison techniques. Findings: – Three dominant themes emerged. Beliefs and attitudes towards cancer and screening represented SA immigrant's perceptions that early detection was beneficial; screening was not necessary in the absence of symptoms; cancer was scary; and the loss of previously established bowel practices upon immigration as potential risks for CRC. Knowledge and awareness focused on unscreened participants' cancer stories; screened participants' knowledge of CRC, risk factors, and screening; experiential learning from focus groups; and screened participants' strategies to promote screening. Support and accessibility concentrated on physician support and responsibility to provide information, explanation, and recommend screening to facilitate access. Originality/value: – Findings provide novel insights on socio-cultural context, beliefs, and barriers to CRC screening among SA immigrants. Culturally appropriate community-based strategies included story-telling, the use of social networks, and greater physician engagement. Enhancing collaborative partnerships with physicians and public health may minimize structural barriers and reduce health disparities. Future research could explore effectiveness of outreach strategies including these collaborations.